Training on CCTV Use and Maintenance at SLB Purnama Asih - Hertog Nugroho; Usman B Hanafiah; Hanny Madiawati; Taufik Irfan; Ferry Satria; Rifa Hanifatunnisa; Nila Novita Sari (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2023)
SLB Purnama Asih is a Special Education School in the Ciwaruga area, just behind the Bandung State Polytechnic campus. There are now 49 students and eight teachers, including the Principal. With a huge number of students and the situation of children who require special monitoring, a monitoring system that can assist instructors in monitoring students in their activities and interactions at school is required. It is important to design and construct a Closed Circuit Television  (CCTV) security system at several school locations to address this. CCTV installation in schools can assist in increasing security and identifying possible threats or criminal activity. It can also assist the school in taking action in an emergency. The procedure that will be followed is installing and training the CCTV security system. The training strategy that will be used is to provide theoretical and practical information. The survey data from 12 respondents, using the Likert approach, revealed that this system was in the excellent range, with a percentage of 96.67%.